Pengaruh Lama Waktu Perendaman Limbah Ekstrak Daun Kersen (Muntingia calabura) Dengan Dosis Sama Terhadap Lama Inkubasi, Daya Tetas dan Kelulushidupan Larva Ikan Lele Dumbo (Clarias gariepinus) - T. Iskandar Johan; Muhammad Hasby; Fakhrunnas MA Jabbar; Hisra Melati; Harni Sri Mulyani (Universitas Riau, 2023)
This research is expected to be useful for fish farmers as additional information in catfish (Clarias gariepinus) aquaculture. The method used is an experimental method using a completely randomized design (CRD) with 5 treatments and 3 replications, namely:P1 = 1 minute immersed in Muntingia calabura leaf extract waste, P2 = 3 minutes immersed, P3 = 5 minutes immersed, P4 = 7 minutes immersed and P5 = 9 minutes immersed. 2.250 eggs of catfish (C. gariepinus) were obtained from artificial spawning of catfish broodstock at the Fish Seed Center, Faculty of Agriculture, Islamic University of Riau. The container used is a jar with a size of 10 liters. Based on the results of research on the effect of immersing waste extracts of M. calabura leaf extract with different immersing times on incubation time, hatchability and survival of catfish larvae, the best treatment was P5, which was 9 minutes of immersion. The parameter results obtained were 92% of egg adhesive, incubation time is 17:24 (17 hours 24 minutes), and hatchability rate is 87.78%. While the results of water quality measurements in this study were classified as optimal for catfish cultivation, with an ammonia range are 0.27-0.75 ppm, DO ranged from 3.14-4.95 mg/l, temperature are 28-31°C and the pH is 6.5.